Fixed points for non-surjective expansion mappings - B. K. Sharma; D. R. Sahu; M. Bounias; A. Bonaly (International Journal of Mathematics and Mathematical Sciences, 1998)
The contractive conditions of Popa (Demonstr. Math. 1990, 23, 213-218) were further improved for four non-surjective expansion mappings, and some common fixed point theorems under semi-compatible pairs of mappings are proved. Our main findings bring improvements to a number of results in the non-metric setting. Some implications for mathematical physics are raised with respect to physical invariants